Transcriptome analysis of responses in Brachypodium distachyon overexpressing the BdbZIP26 transcription factor - Ruth C. Martin; Brent A. Kronmiller; James E. Dombrowski (BMC Plant Biology, 2020)
Abstract Background Biotic and abiotic stresses are the major cause of reduced growth, persistence, and yield in agriculture. Over the past decade, RNA-Sequencing and the use of transgenics with altered expression of stress related genes have been utilized to gain a better understanding of the molecular mechanisms leading to salt tolerance in a variety of species. Identification of transcription factors that, when overexpressed in plants, improve multiple stress tolerance may be valuable for crop improvement, but sometimes overexpression leads to deleterious effects during normal plant growth. Results Brachypodium constitutively expressing the BdbZIP26:GFP gene showed reduced stature compared to wild type plants (WT). RNA-Seq analysis comparing WT and bZIP26 transgenic plants revealed 7772 differentially expressed genes (DEGs). Of these DEGs, 987 of the DEGs were differentially expressed in all three transgenic lines. Many of these DEGs are similar to those often observed in response to abiotic and biotic stress, including signaling proteins such as kinases/phosphatases, calcium/calmodulin related proteins, oxidases/reductases, hormone production and signaling, transcription factors, as well as disease responsive proteins. Interestingly, there were many DEGs associated with protein turnover including ubiquitin-related proteins, F-Box and U-box related proteins, membrane proteins, and ribosomal synthesis proteins. Transgenic and control plants were exposed to salinity stress. Many of the DEGs between the WT and transgenic lines under control conditions were also found to be differentially expressed in WT in response to salinity stress. This suggests that the over-expression of the transcription factor is placing the plant in a state of stress, which may contribute to the plants diminished stature. Conclusion The constitutive expression of BdbZIP26:GFP had an overall negative effect on plant growth and resulted in stunted plants compared to WT plants under control conditions, and a similar response to WT plants under salt stress conditions. The results of gene expression analysis suggest that the transgenic plants are in a constant state of stress, and that they are trying to allocate resources to survive.